Diagnostic accuracy of power Doppler ultrasound in patients with chronic tennis elbow. Issue 11 (28th February 2008) - du Toit, C; Stieler, M; Saunders, R; Bisset, L; Vicenzino, B
Abstract : Objective: To determine the diagnostic accuracy of power Doppler and grey scale ultrasonography, assess the relationship between severity measures and neovascularity, and describe the intra-tendon distribution of neovascularity in chronic tennis elbow. Design: Between group cross sectional study. Setting: Sports medicine clinic and radiology centre. Participants: 32 affected elbows (median and range of duration: 10; 3–120 months) and 18 unaffected contralateral elbows in 25 patients (mean age 50 years) with lateral elbow pain, and 38 unaffected elbows in 19 asymptomatic participants (mean age 45 years) underwent a clinical examination (reference standard test) and grey scale and power Doppler ultrasonographic examination. Main outcome measures: Ultrasound examination with power Doppler identified neovascularity and grey scale ultrasound changes (lateral epicondyle bony spurring or irregularity, maximum anterior–posterior thickness, and echo characteristics) of the common extensor tendon. Results: Power Doppler had a strong positive likelihood ratio of 45.39, whereas a combined null finding in power Doppler and grey scale ultrasonography resulted in a robust negative likelihood ratio of 0.05. Grey scale changes were generally not as diagnostically accurate. Common extensor tendon neovascularity was equally distributed between the superficial and deep part of the tendon, and clinical severity measures did not correlate with neovascularity scores. Conclusions: Neovascularity identified with power Doppler ultrasonography when compared to grey scale changes (alone or in combination with Doppler) was diagnostically superior in identifying chronic tennis elbow. The lack of both neovascularity and grey scale changes on ultrasound examination also substantially increase the probability that the condition is not present and should prompt the clinician to consider other causes for lateral elbow pain.